Identifikasi Senyawa Flavonoid Daun Dempul Lelet (Glochidion rubrum BI) - Firawati, Firawati; Hasrida (Universitas Islam Negeri Alauddin Makassar, 2023)
Dempul lelet (Glochiodion rubrum BI) still quite foreign to hear, but for women, this plant is quite popular because it can be used as cosmetics. Its use as a cosmetic indicates the presence of antioxidant compounds contained in the leaves so identification is carried out. The thin layer chromatography and infrared spectrophotometry methods used showed that the presence of flavonoids in fraction A was indicated by the presence of OH groups at an absorption of 3452.58 cm-1, aliphatic C-H at an absorption of 2954.94 cm-1, C=O group at an absorption of 1811.16 cm-1 , and C=C aromatic group at an absorption of 1643.35 cm-1.